Complex PTSD among treatment-seeking veterans with PTSD - Letica-Crepulja, Marina (Eur J Psychotraumatol, 2020)
Background: In the ICD-11 hierarchical classification structure, posttraumatic stress disorder (PTSD) and complex PTSD (CPTSD) are separate and distinct but also ‘sibling’ disorders, meaning that the diagnoses follow from the parent category of traumatic stress disorders. Objective: The aim of this study was to examine the prevalence of CPTSD in treatment-seeking war veterans with PTSD more than 20 years after the exposure to cumulative war-related trauma(s). The second aim was to examine if there was an association between demographic and psychosocial variables and CPTSD or PTSD. Method: A sample of 160 male war veterans with PTSD referred to the outpatient service of the PTSD Referral Centre at the Clinical Hospital Centre (CHC) Rijeka participated in a cross-sectional study. Psychiatric comorbidity was assessed using the Mini-International Neuropsychiatric Interview (MINI) and participants completed validated self-report measures: The Life Events Checklist for DSM-5 (LEC-5), International Trauma Questionnaire (ITQ). Results: In total, 80.63% of the sample met criteria for a probable diagnosis of CPTSD. The study revealed that there was no significant difference in the length of deployment, in the intensity of the PTSD symptoms, types of trauma exposure and pharmacotherapeutic treatment between PTSD and CPTSD group. It was found that veterans with PTSD were more likely to be divorced and to participate in PTSD clubs. On the other hand, veterans with CPTSD were significantly more likely to have higher levels of functional impairment and comorbidity with general anxiety disorder (GAD) compared to the PTSD group. Conclusions: This study supports the proposition that a prolonged trauma of severe interpersonal intensity such as war is related to high rates of CPTSD among treatment-seeking veterans, years after the war. The distinction between PTSD and complex PTSD may help the selection of person-centred treatment interventions that would target specific mental health and functional problems in patients.